ANALISIS FRAMING PEMBERITAAN KEBIJAKAN PENUTUPAN TIKTOK SHOP PADA ANTARA NEWS PERIODE OKTOBER 2023 - Prayoga, Muhammad Damara Shadiq; Patriantoro, Patriantoro; Sanulita, Henny (Universitas Tanjungpura, 2025)
This study aims to analyze the framing in the syntactic, script, thematic, and rhetorical structures contained in the news coverage of the TikTok Shop closure policy by ANTARA News in the October 2023 period. The method used is descriptive method with qualitative form. The data sources in this study are 17 news texts regarding the TikTok Shop closure policy published by ANTARA News in the October 2023 period. The data collection techniques used documentary study techniques. Based on the research results on the syntactic structure, there are 17 headlines, 17 leads, 29 background information, 64 source quotes, and 28 closings. In the script structure, there are 4 news with prominent what elements, 7 news with prominent why elements, 1 news with prominent who elements, and 5 news with prominent how elements. In the thematic structure, 13 elements of detail, 13 elements of purpose, 12 elements of coherence, 13 active sentences, 6 passive sentences, then 7 thirdperson singular pronouns, 13 first-person plural pronouns, 5 thirdperson plural pronouns, and 7 first-person singular pronouns were found. In the rhetorical structure, 30 lexicons, 12 graphics, and 6 metaphors were found. This research is expected to contribute to language research that focuses on the interpretation of media texts.